Molecular prevalence, genetic characterization and patterns of Toxoplasma gondii infection in domestic small mammals from Cotonou, Benin - (:unkn) unknown (My University, 2022)
This study is part of a long-term partnership between Cotonou Autonomous Seaport, the Polytechnic School of Abomey-Calavi, the French Institute of Research for Sustainable Development, and the Tropical Neurology Institute (Inserm U1094, IRD U270 EpiMaCT, University of Limoges). We are grateful to Ladji, Agla and Saint-Jean authorities as well as inhabitants who kindly authorized us to access their households for trapping and interview purposes. We thank the Autonomous Port of Cotonou authorities and staff who facilitated our access to their infrastructures. We also thank the CBGP Small Mammal Collection (Centre de Biologie pour la Gestion des Populations, 2018, “CBGP – Small mammal Collection”, https://doi.org/10.15454/WWNUPO) for the conservation of samples from Benin.
Keywords: African Research